The Meaning of Environmental Awareness Messages Signs through Film: Semiotic Analysis of Spirited Away Film - Vien Audrey (Budapest International Research and Critics University, 2022)
Environmental awareness is an issue that has never ended until now, both in the natural environment, social environment, and artificial environment. Global warming and crime rates that continue to increase are clear evidence that there are still many people who are not aware of the critical role of humans in protecting the environment. The film